2007
DOI: 10.1159/000110661
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intracranial Meningiomas – Do They Differ from Their Counterparts in Adults?

Abstract: Aim: Meningiomas are very rare in children comprising only 0.44.1% of pediatric age tumors and only 1.5–1.8% of all intracranial neoplasms. We analyzed the clinical, pathological and management profile of these rare tumors and elucidated their differences from meningiomas in adults. Methods: From 1990 to 2005, 33 patients belonging to the pediatric age group with intracranial meningiomas were treated in NIMHANS. Results: There were 19 male and 14 female children. The duration of symptoms ranged from 1 to 60 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 39 publications
2
61
0
7
Order By: Relevance
“…However, some reports indicated that recurrence was very common for high-grade lesions, even following complete resection (1,7,8). Our case is consistent with these latter reports, as, although gross total excision of the tumor was possible, the tumor reappeared in the same location 2 months later.…”
Section: Discussionsupporting
confidence: 91%
“…However, some reports indicated that recurrence was very common for high-grade lesions, even following complete resection (1,7,8). Our case is consistent with these latter reports, as, although gross total excision of the tumor was possible, the tumor reappeared in the same location 2 months later.…”
Section: Discussionsupporting
confidence: 91%
“…In a series of 675 adult meningiomas reported by Liu et al [7], only 3.7% were intraventricular. In 4 pediatric series of 98 combined cases, 19 (19.4%) were intraventricular [1,2,7,8]. Ney et al [9] reported an intraventricular meningioma that developed 23 years after cranial irradiation for acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…There are also disparate epidemiological qualities between the two groups with less significant female preponderance within the pediatric population [1,4]. Some studies attribute a similar incidence to both sexes, while others suggest a higher incidence among male children [1,3,5,6]. The reason for this variation of incidence between pediatric and adult meningiomas is unknown but is perhaps suggestive of different pathophysiologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric age group, this type of tumor is considerably rarer, making up roughly 2% of all pediatric CNS tumors [1,3]. A variant of the pediatric meningioma that is even more uncommon is that found to be completely intra-axial (intraparenchymal) and to arise without dural attachments.…”
Section: Introductionmentioning
confidence: 99%